2003
DOI: 10.1093/jb/mvg223
|View full text |Cite
|
Sign up to set email alerts
|

Two Nuclear Export Signals Specify the Cytoplasmic Localization of Calcineurin B Homologous Protein 1

Abstract: We previously showed that calcineurin B homologous protein 1 (CHP1) interacts with nuclear apoptosis-inducing protein kinase DRAK2, and that overexpression of DRAK2 induces the nuclear accumulation of CHP1, although CHP1 usually resides in the cytoplasm [Matsumoto et al. (2001) J. Biochem. 130, 217-225]. Here we show that CHP1 has two functional nuclear export signal (NES) sequences in its carboxyl-terminal region. Treatment of several cell lines with leptomycin B, a specific inhibitor of CRM1-dependent nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, in A. nidulans, there are several arguments against this hypothesis: (i) computer analysis † of the amino acid sequence of both HapC and HapE did not reveal any obvious NES sequence. 29 The same was concluded on the basis of the NES consensus sequence defined by Nagita et al 30 However, since NESs are poorly defined, the HapC amino acid sequence shows a region of some similarity to the NES consensus found for Nap1p from S. cerevisiae, 29 whereas HapE does not contain such a sequence. Even if the putative HapC NES were functional, it would be present in HapC and not HapE and therefore, its presence would not support the hypothesis of an NES present in a HapE homolog.…”
Section: Discussionsupporting
confidence: 55%
“…However, in A. nidulans, there are several arguments against this hypothesis: (i) computer analysis † of the amino acid sequence of both HapC and HapE did not reveal any obvious NES sequence. 29 The same was concluded on the basis of the NES consensus sequence defined by Nagita et al 30 However, since NESs are poorly defined, the HapC amino acid sequence shows a region of some similarity to the NES consensus found for Nap1p from S. cerevisiae, 29 whereas HapE does not contain such a sequence. Even if the putative HapC NES were functional, it would be present in HapC and not HapE and therefore, its presence would not support the hypothesis of an NES present in a HapE homolog.…”
Section: Discussionsupporting
confidence: 55%
“…Although it is well established that the dephosphorylation of Crz1p by calcineurin leads to its nuclear translocation (Stathopoulos‐Gerontides et al ., 1999), there are no reports of the nuclear localization of calcineurin B in the yeasts or filamentous fungi. Nuclear localization of a calcineurin B homologous protein (CHP1) has been reported (Nagita et al ., 2003; Jiménez‐Vidal et al ., 2010). We could not identify any potential NLS sequence in the A. fumigatus CnaB and it is possible that CnaB may translocate into the nucleus with CnaA and CrzA.…”
Section: Discussionmentioning
confidence: 99%
“…1996). Only one functional NES (aa 137–148) was identified in CHP2, although several studies have reported two putative NES (Nagita et al. 2003).…”
Section: Discussionmentioning
confidence: 99%